A systematic study on dysregulated microRNAs in cervical cancer development. Issue 6 (12th June 2015) - He, Yuqing; Lin, Juanjuan; Ding, Yuanlin; Liu, Guodong; Luo, Yanhong; Huang, Mingyuan; Xu, Chengkai; Kim, Taek‐Kyun; Etheridge, Alton; Lin, Mi; Kong, Danli; Wang, Kai
Abstract : MicroRNAs (miRNAs) are short regulatory RNAs that modulate the transcriptome and proteome at the post‐transcriptional level. To obtain a better understanding on the role of miRNAs in the progression of cervical cancer, meta‐analysis and gene set enrichment analysis were used to analyze published cervical cancer miRNA studies. From 85 published reports, which include 3, 922 cases and 2, 099 noncancerous control tissue samples, 63 differentially expressed miRNAs (DEmiRNAs) were identified in different stages of cervical cancer development (CIN 1‐3 and CC). It was found that some of the dysregulated miRNAs were associated with specific stages of cervical cancer development. To illustrate the impact of miRNAs on the pathogenesis of cervical cancer, a miRNA‐mRNA interaction network on selected pathways was built by integrating viral oncoproteins, dysregulated miRNAs and their predicted/validated targets. The results indicated that the deregulated miRNAs at the different stages of cervical cancer were functionally involved in several key cancer related pathways, such as cell cycle, p53 and Wnt signaling pathways. These dysregulated miRNAs could play an important role in cervical cancer development. Some of the stage‐specific miRNAs can also be used as biomarkers for cancer classification and monitoring the progression of cancer development.